Effects of acupuncture and nicotine patch on smoking: a multicenter, randomized, controlled, double-blind clinical trial - Dai, Runjing; Ren, Dong; Li, Binning; Zhang, Yanfeng; Ma, Xiaojing; Zhang, Xiangrong; Zhang, Hailiang; Zhang, Lina; Zeng, Chenchen; Jiang, Xiaomei; Bao, Shisan; Fan, Jingchun (Frontiers in Medicine, 2024)
Aims To evaluate the effects of acupuncture and/or nicotine patches on smoking cessation. Methods Eighty-eight participants were randomly allocated into four groups: acupuncture combined with nicotine patch (ACNP), acupuncture combined with sham nicotine patch (ACSNP), sham acupuncture combined with nicotine patch (SACNP), and sham acupuncture combined with sham nicotine patch (SACSNP). The primary outcome was self-reported smoking abstinence verified with expiratory Carbon Monoxide (CO) after 8 weeks of treatment. The modified Fagerstrom Test for Nicotine Dependence (FTND) score, Minnesota Nicotine Withdrawal Scale (MNWS), and the Brief Questionnaire of Smoking Urge (QSU-Brief) score were used as secondary indicators. SPSS 26.0 and Prism 9 software were used for statistical analyses. Results Seventy-eight participants completed the study. There were no significant differences in patient characteristics at baseline across the four groups. At the end of treatment, there was a statistically significant difference (χ2 = 8.492, p = 0.037) in abstaining rates among the four groups. However, there were no significant differences in the reduction in the number of cigarettes smoked daily (p = 0.111), expiratory CO (p = 0.071), FTND score (p = 0.313), and MNWS score (p = 0.088) among the four groups. There was a statistically significant difference in QUS-Brief score changes among the four groups (p = 0.005). There was no statistically significant interaction between acupuncture and nicotine patch. Conclusion Acupuncture combined with nicotine replacement patch therapy was more effective for smoking cessation than acupuncture alone or nicotine replacement patch alone. No adverse reactions were found in the acupuncture treatment process. Clinical trial registration http://www.chictr.org.cn/showproj.aspx?proj=61969, identifier ChiCTR2100042912.